2011
DOI: 10.1162/rest_a_00061
|View full text |Cite
|
Sign up to set email alerts
|

Is Labor Mobility a Channel for Spillovers from Multinationals? Evidence from Norwegian Manufacturing

Abstract: © Dette eksemplar er fremstilt etter avtale med KOPINOR, Stenergate 1, 0050 Oslo. Ytterligere eksemplarfremstilling uten avtale og i strid med åndsverkloven er straffbart og kan medføre erstatningsansvar. MNE-experience contribute 20% more to the productivity of their plant than workers without experience from MNEs, even after controlling for differences in unobservable worker characteristics. The difference between the private returns to mobility and the productivity effect at the plant level suggests that la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
177
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(191 citation statements)
references
References 35 publications
10
177
2
2
Order By: Relevance
“…We cannot identify these imperfections, but they must be truly large to sustain the abnormally high rents to the hiring firms implied by our results: $2.3 $4 return on each dollar invested in attracting SPs. On the other hand, we can support the first interpretation, based on uncertainty regarding workers' spillover potential, by applying the decomposition in (6) to the results in Balsvik (2011), whose data and method are comparable to ours, except for one difference, that the SPs in her study are the workers with foreign firm experience hired by domestic firms. Because this experience, unlike the productivity gap, is a highly visible characteristic, their spillover potential should be better recognized and rewarded.…”
Section: Gains Distributionsupporting
confidence: 65%
See 2 more Smart Citations
“…We cannot identify these imperfections, but they must be truly large to sustain the abnormally high rents to the hiring firms implied by our results: $2.3 $4 return on each dollar invested in attracting SPs. On the other hand, we can support the first interpretation, based on uncertainty regarding workers' spillover potential, by applying the decomposition in (6) to the results in Balsvik (2011), whose data and method are comparable to ours, except for one difference, that the SPs in her study are the workers with foreign firm experience hired by domestic firms. Because this experience, unlike the productivity gap, is a highly visible characteristic, their spillover potential should be better recognized and rewarded.…”
Section: Gains Distributionsupporting
confidence: 65%
“…Hiring SPs will increase output because they are more productive, but there may also be extra costs due to higher input prices, labor in particular. Indeed, the wages of both worker types are likely to be affected, as SPs may receive a premium reflecting the knowledge they bring (Balsvik, 2011), and non SPs may benefit by learning from SPs (Poole, 2013) or through wage bargaining actuated by fairness concerns (Smith, 2012). The profit after hiring SPs is…”
Section: Output Gains Distribution Between Firms and Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, researchers (e.g., Aitken et al, 1996) found that positive wage spillovers were more likely in developed nations where firms have the requisite 'absorptive capacity' (Cantwell, 1993). And a number of recent studies have combined premise and employee level data in order to support the existence of positive spillovers to employee wages in transition nations (e.g., Smarzynska-Javorcik, 2004), developing nations (e.g., Görg & Strobl, 2005;Poole, 2013), and developed nations (e.g., Andrews et al, 2009;Balsvik, 2011).…”
Section: Background Literaturementioning
confidence: 99%
“…5 Existing empirical work is consistent with the idea that workers learn from foreign managers, but suggests that spillovers to other firms and workers are small in developing countries. Balsvik (2011) finds that in Norway workers with experience working for a MNE contribute 20% more to plant productivity than comparable workers without MNE experience. Poole (2012) finds that Brazilian firms which employ a higher share of workers with previous experience at MNEs pay higher wages, even after controlling for worker, firm and time fixed effects.…”
Section: Introductionmentioning
confidence: 96%